2010
DOI: 10.1371/journal.pone.0009507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmaceutical Potential Endocrine Disruptor Compounds on Protein Disulfide Isomerase Reductase Activity Using Di-Eosin-Oxidized-Glutathion

Abstract: BackgroundProtein Disulfide Isomerase (PDI) in the endoplasmic reticulum of all cells catalyzes the rearrangement of disulfide bridges during folding of membrane and secreted proteins. As PDI is also known to bind various molecules including hormones such as estradiol and thyroxin, we considered the hypothesis that adverse effects of endocrine-disrupter compounds (EDC) could be mediated through their interaction with PDI leading to defects in membrane or secreted proteins.Methodology/Principal FindingsTaking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In a previous paper 5 , we reported that two non-oestrogenic steroids, MPA, and 19-NT potentiated PDI reductase activity. Even with a somewhat limited screening, in the present study we were able to identify a few other molecules also potentiating PDI reductase activity using the recently developed assay with DiE-GSSG as substrate 6 .…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…In a previous paper 5 , we reported that two non-oestrogenic steroids, MPA, and 19-NT potentiated PDI reductase activity. Even with a somewhat limited screening, in the present study we were able to identify a few other molecules also potentiating PDI reductase activity using the recently developed assay with DiE-GSSG as substrate 6 .…”
Section: Discussionmentioning
confidence: 78%
“…To our knowledge, this paper and the previous one from our laboratory 5 are the first to describe ligands that potentiate PDI activity. Molecules with such a potentiating effect on PDI activity would be of utmost interest for the treatment of pathologies originating from intracellular protein aggregation.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations